The Effect of Capital Productivity Management on Capital Asset Pricing Models with a Focus on Life Cycle - ali alimohammadpour; ali zabihi; khosro Faghani Makrani (مدیریت بهره وری, 2020)
Capital productivity concerns the measurement of management power in making optimal use of capital as one of the important and limited company resources. In companies with highly efficient capital productivity, stocks are expected to offer higher returns and the explanatory power of the models proposed to predict stock returns is assumed to increase. The purpose of this study was, thus, to examine the extent to which capital productivity might influence the explanatory power of stock market predictive models and to scrutinize this viable effect at various stages of corporate life cycle. The Operating Profit Ratio (ROIC) was used to operationalize Capital productivity, the Tripartite Factor Model (Fama & Franch, 1993) and the Pentagonal Factor Model (Fama & Franch, 2013) were employed to predict stock returns and corporate life cycle was categorized via the Dickinson Cash Flow (2011). The research sample comprised 110 companies with specific descriptive characteristics selected from among all those listed on the Tehran Stock Exchange during a ten-year period from 2005 to 1394. The results of the hypothesis testing analyses demonstrated that capital productivity affects the relationship between market factor and risk-free growth at all stages of the life cycle, but size was found significantly correlated with risk merely at the maturity stage of the life cycle.